2019
DOI: 10.1115/1.4045494
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Kinematic and Contact Force Modeling of a Human Finger Tendon System Using Bond Graphs and Robotic Validation

Abstract: This paper aims to use bond graph modeling to create the most comprehensive finger tendon model and simulation to date. Current models are limited to either free motion without external contact or fixed finger force transmission between tendons and fingertip. The forward dynamics model, presented in this work, simultaneously simulates the kinematics of tendon-finger motion and contact forces of a central finger given finger tendon inputs. The model equations derived from bond graphs are accompanied by nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Because cadaver experimentation is subject to time and experimental constraints, computational models or robotic testbeds could conduct more extensive investigations into tendon biomechanics. Many computational and robotic hand models are limited, but recent developments from the authors (Tigue, King, & Mascaro, 2020a;Tigue, Rockwell, Foreman, & Mascaro, 2020b) demonstrate further anatomical accuracy of finger tendon modeling and robotic recreations. This article also provides experimental data for future development and validation of these tools for investigating human hand reconstructive tendon surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Because cadaver experimentation is subject to time and experimental constraints, computational models or robotic testbeds could conduct more extensive investigations into tendon biomechanics. Many computational and robotic hand models are limited, but recent developments from the authors (Tigue, King, & Mascaro, 2020a;Tigue, Rockwell, Foreman, & Mascaro, 2020b) demonstrate further anatomical accuracy of finger tendon modeling and robotic recreations. This article also provides experimental data for future development and validation of these tools for investigating human hand reconstructive tendon surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…( a ) Extensor mechanism, ( b ) corresponding mechanical representation and ( c ) the BG representation of the extensor mechanism, reproduced from Tigue et al . [42]. …”
Section: Bg Modelling In Biology and Physiologymentioning
confidence: 99%
“…However, the speed of the entire hand or of the consequently moving virtual object may not be sufficient to reflect the force from the user's hand. In some robotics studies, the speed of each finger joint is applied biologically by the grip force of the hand connected to the forearm muscle [31,32]. Iyengar et al [31] confirmed that the moving speed of the arm affects the grip force of the fingers.…”
Section: Motion Speed In Grip-lift Interactionsmentioning
confidence: 99%
“…Iyengar et al [31] confirmed that the moving speed of the arm affects the grip force of the fingers. In another study by Tigue et al [32], a finger tendon model and its simulation were developed using the Bond graph modeling method. Biomechanical modeling was used, which reflected each finger's speed based on the movement of fingers by the tendon initiating from the forearm connected to the hand [32].…”
Section: Motion Speed In Grip-lift Interactionsmentioning
confidence: 99%
See 1 more Smart Citation